VD_FINDINFO HC / 2010 / 554 vom 3. September 2010 - VD Tribunal cantonal (2010)
ESCROQUERIE, ESCROQUERIE EN MATIÈRE DE PRESTATIONS, FIXATION DE LA PEINE | 146 al. 1 CP, 47 CP, 411 let. h CPP, 411 let. i CPP, 415 CPP